Gambaran Respon Time Pasien Instalasi Gawat Darurat di RSIA Bunda Denpasar - I Putu Arya Wijayantha; Putu Desi Yulistina; Putu Sundari Dewi (Jurnal Kesehatan Amanah, 2025)
Response time in the Emergency Room (IGD) is an important indicator in determining the quality of health services, especially in situations that require fast and appropriate treatment. This study aims to describe the response time of patients in the emergency room at RSIA Bunda Denpasar. This research uses a descriptive design with an observational approach. The population in this study were all patients who came to the emergency room at RSIA Bunda Denpasar during the research period, with the sample taken being total sampling. Data was collected through direct observation of the response time from patient admission to first treatment by medical personnel. Research Results: The total number of patients served in the ER that month was 184 people, with the following triage distribution: triage 1 (0 patients), triage 2 (108 patients or 58.7%), triage 3 (73 patients or 39.7%), and triage 4 (3 patients or 1.6%). In terms of gender, there were more female patients (105 people) than male patients (79 people). Most of the patients were over 18 years old (117 people or 63.6%). Response time data shows that 100% of patients receive service within ≤ 5 minutes. The conclusion of this study shows that the Emergency Room at RSIA Bunda Denpasar has an optimal response time where all patients are served within ≤ 5 minutes. This reflects the readiness of medical personnel and good emergency room facilities to treat patients quickly and efficiently.